Child-Friendly Schools in Primary Education Institutions - Rahmad, Rahmad; Inayah Syar, Nur; Syahmidi, Syahmidi; Mualimin , Mualimin (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study aims to identify the implementation of five indicators of Child-Friendly Schools at SDN SN Karang Mekar 1, Banjarmasin City. This study's research type is qualitative descriptive research, utilizingmethods such as interviews, observations, and document analysis. This study found that the written policy indicators have been well implemented by declaring a commitment to non-violence and creating a safe student environment. Child-friendly learning processes are implemented with a non-violent and fun approach, supporting an inclusive learning atmosphere. Training for teachers on children's rights has created a school atmosphere that supports students' holistic development. Although school facilities are adequate, improved accessibility for children with special needs is still needed. In addition, students' participation in extracurricular activities is good, but their decision-making involvement still needs improvement. The implications of the findings suggest the need for more robust policies, continuous training, and improved infrastructure and student participation to realize entirely child-friendly schools.